The Teaching Practices of Senior High School English Teachers in Maguindanao, Philippines - Saima A. Sansaluna-Maulana (RIRAI Publisher, 2021)
This study determined the teaching practices of the English teachers teaching in Senior High School in Maguindanao in terms of instructional competence, professional and personal characteristics, and punctuality and attendance. The descriptive-correlational survey method was used to determine the significant relationship of the level of teaching practices of the senior high English teachers and the students’ level of academic performance. Results revealed that the Senior High School English Teachers’ level of teaching practices in terms of instructional competence, professional and personal characteristics, and punctuality and attendance are very satisfactory. The Senior High School students’ level of academic performance in English is also very satisfactory. Results also show that there is no significant relationship between the teachers’ level of teaching practices in terms of instructional competence, professional and personal characteristics, and their students’ level of academic performance in English. In contrast, findings show that there is a significant relationship between the teachers’ level of teaching practices in terms of punctuality and attendance and their students’ level of academic performance in English. Thus, the Senior High School English Teachers’ level of teaching practices is influenced by their punctuality and attendance and the teachers’ punctuality and attendance contributed to students’ level of academic performance in English.